¿Cómo escribimos los abogados? : la enseñanza del lenguaje jurídico - De Cucco Alconada, María Carmen (2016)
A modern justice is a justice available to every citizen, regardless of his or her background or education. Availability is utterly determined by the language used by lawyers and judges in their practise. Unclear and diffuse communication generates mistrust, and increases distance between the judiciary system and common people. Thus, the Movement of the Plain Style, which claims that all regulations should be written in an understandable way for those who have them to comply, is to be taken into account. In this line of thought is that it's precise to pay attention to legal writing and it's teaching, mainly during Law School. In this paper we advocate for the inclusion of interdisciplinary courses which provide students with writing tools, focusing on the communicative function of language.